2009
DOI: 10.1007/s00181-009-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the evidence on PPP: a systematic investigation into MA roots in panel unit root tests and their implications

Abstract: Abstract:Panel unit root tests of real exchange rates -as opposed to univariate tests -usually reject non-stationarity. These tests, however, could be biased if the real exchange rate contained MA roots. Indeed, two independent arguments claim that the real exchange rate, being a sum of a stationary and a non-stationary component, is possibly an ARIMA (1, 1, 1) process. Monte Carlo simulations show, how systematic changes in the parameters of the components, of the test equation and of the correlation matrix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Zou et al (2008), for example, propose a lifecycle risk management framework which emphasizes the dynamic process for allocating and monitoring risks in all stages. Fischer and Porath (2010) developed an integrated risk management system to cover different perspectives of the stakeholders involved. Wang et al (2004) identified three main stages of risk management: (1) risk identification of relevant and potential risks, (2) risk analysis and evaluation of the potential impact; and (3) risk response in order to formulate suitable risk treatment strategies or mitigation measures.…”
Section: Risk Managementmentioning
confidence: 99%
“…Zou et al (2008), for example, propose a lifecycle risk management framework which emphasizes the dynamic process for allocating and monitoring risks in all stages. Fischer and Porath (2010) developed an integrated risk management system to cover different perspectives of the stakeholders involved. Wang et al (2004) identified three main stages of risk management: (1) risk identification of relevant and potential risks, (2) risk analysis and evaluation of the potential impact; and (3) risk response in order to formulate suitable risk treatment strategies or mitigation measures.…”
Section: Risk Managementmentioning
confidence: 99%
“…The appropriateness of different indices in reflecting price competitiveness of an economy has been discussed inter alia in Deutsche Bundesbank (1998Bundesbank ( , 2004 and ECB (2003aECB ( , 2005a. According to the Bundesbank studies, a rather broadly defined price index such as the price deflator of total sales should be the most suitable since such indicators are the only ones that reflect price differentials in intermediate inputs that make up a significant part of differences in price Bearing in mind the possible limitations of their adequacy as expressed in Banerjee et al (2004Banerjee et al ( , 2005 and Fischer/Porath (2006), panel unit root tests of the country panels of real effective exchange rates have been performed. Real exchange rates are often found to be correlated (cf O'Connell, 1998, for example), a property which will obviously also pertain to real effective exchange rates which are just weighted averages of the former.…”
Section: Relative Pppmentioning
confidence: 99%
“…The four DF and the ADF panel cointegration test statistics ofKao (1999) have been used as well as three (tests 2-4 of his Table 1, p 660) of those developed byPedroni (1999).9 This could be due to biases which typically arise in real exchange rate series, as suggested byFischer/Porath (2006).…”
mentioning
confidence: 99%